The Influence of Marketing Mix (7P) on Patient Satisfaction in Hospital: A Systematic Literatur Review - Yusron, Ahmad; Rohmah, Nur; Ningsih, Riyan (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Helathcare services in hospitals are rapidly developing. To cope with these changes, hospitals are required to implement optimal strategies to compete and adapt. Hospital marketing is becoming increasingly competitive worldwide. Marketing mix stategy is considered one of the core concepts of marketing theory. Objective : to analyze the effect of the marketing mix on patient satisfaction in various hospital Research Methods/ Implementation Methods : A systematic Review. Search from Google Scholar, Pubmed, Google, Portal Garuda with search keywords marketing mix, patient satisfaction and hospital. From 70 articles obtained, then the articles used were articles that met the inclusion criteria. Results : Overall, the resulta of this literature review indicate that the implememtation of a comprehensive marketing mix strategy plays an important role in improving patient satisfaction and indicates that patient satisfaction can be optimized through integrated management of marketing mic components Conclusion/Lesson Learned : All articles studied show the results of the influence of the marketing mix (product, price, place, promotion, people, process, physical evidence) on patient satisfaction in hospitals